VD_FINDINFO Plainte / 2019 / 33 vom 2. Juli 2019 - VD Tribunal cantonal (2019)
SAISIE DE SALAIRE, QUOTITÉ SAISISSABLE, MINIMUM VITAL, OBLIGATION D'ENTRETIEN, MAJORITÉ{ÂGE}, ENFANT | 277 al. 2 CC, 18 al. 1 LP, 93 al. 1 LP